Age and Sex: Impact on adipose tissue metabolism and inflammation. (October 2021) - Varghese, Mita; Song, Jianrui; Singer, Kanakadurga
Highlights: Adipose tissue dysfunction related inflammation contributes to chronic disease and adverse health outcomes with advancing age. Aging is associated with increased visceral adiposity, aberrant adipogenesis, altered adipokine secretion and insulin resistance. Sex differences are observed in adipose tissue re-modeling, collagen deposition and cellular senescence in aging. Age-related changes in sex steroid hormones lead to changes in immune cell numbers and function of macrophages, dendritic cells, and T and B cells. Countermeasures targeting adipose tissue offer promise to reduce the burden of age-associated metabolic diseases and increase longevity. Abstract: Age associated chronic inflammation is a major contributor to diseases with advancing age. Adipose tissue function is at the nexus of processes contributing to age-related metabolic disease and mediating longevity. Hormonal fluctuations in aging potentially regulate age-associated visceral adiposity and metabolic dysfunction. Visceral adiposity in aging is linked to aberrant adipogenesis, insulin resistance, lipotoxicity and altered adipokine secretion. Age-related inflammatory phenomena depict sex differences in macrophage polarization, changes in T and B cell numbers, and types of dendritic cells. Sex differences are also observed in adipose tissue remodeling and cellular senescence suggesting a role for sex steroid hormones in the regulation of the adipose tissue microenvironment. It is crucial to investigate sex differences in aging clinical outcomes to identify and better understand physiology in at-risk individuals. Early interventions aimed at targets involved in adipose tissue adipogenesis, remodeling and inflammation in aging could facilitate a profound impact on health span and overcome age-related functional decline.